Analysis on physical and microstructural properties of ZTA-SWNT ceramic cutting tool - Abdul Molok, Salma; Hamidon, Nor Ezzati; Ahmad Azhar, Ahmad Zahirani; Manshor, Hanisah; Rejab, Nik Akmar; Ahmad, Zainal Arifin; Mohd. Ali, Afifah (AIP Publishing, 2019)
The development of advanced cutting tools for the industrial sectors required materials that can provide a high performance in term of its microstructure, hardness and fracture toughness. Therefore, continuous improvement of ZTA cutting tool is aimed in this research. The purpose of this study is to investigate the effect of single-walled nanotubes (SWNT) addition on physical and microstructural properties of ZTA cutting tools. Ceramic composites with compositions of 80wt. % of Al2O3 and 20 wt. % YSZ were added with varied amount of SWNT which are 0.05, 0.1, 0.3 and 0.5 wt. %.The SWNT was soaked in 20 mL ethanol under ultrasonic condition for 1 hour and mixed with the composition. These batch of compositions were ball milled for 24 hours before properly dried and powdered. The powder is then pressed into round-shaped cutting inserts mold by the uniaxial pressure of 100 MPa. The prepared samples were sintered at 1600 ºC for 4 hours soaking time under pressureless condition. The bulk density and porosity of the sintered sample was identified and SEM images are used to analyse the microstructure of the sample. The effect of SWNT addition was observed on the bulk density, porosity, and microstructure of the sintered samples. The results indicated that the addition of 0.1 wt. % of SWNT to the composite, the highest bulk density of 3.987 g/cm3 was obtained. The small addition of SWNT (< 0.1 wt. %) formed a bridging effect with the Al2O3 and ZrO2 particles. The maximum value of SWNT can be added is 0.1 wt. % where further additions of the SWNT to the composition will reduce the properties of the ZTA cutting tool.